Empowering Innovation: How Self-Leadership and Inclusive Leadership Shape Creative Work Behavior - Suryana, Chacha Anggi; Pareke, Fahrudin JS (Universitas Negeri Semarang, 2025)
This study investigates the influence of self-leadership and inclusive leadership on innovative work behavior, with creative self-efficacy as a mediating variable within a retail organizational contex. This research is important considering the dynamics of the increasingly fierce retail industry competition requires companies to continue to innovate through human resource empowerment, especially in developing leadership styles that are able to trigger employee creativity and initiative. Drawing on a sample of 213 employees from PT Indomarco Prismatama in Bengkulu City, Indonesia, the research employs a quantitative approach using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that self-leadership and inclusive leadership significantly enhance employees' creative self-efficacy, positively affecting their innovative work behavior. Moreover, creative self-efficacy mediates the relationship between leadership styles and innovation, indicating its central role in fostering workplace creativity. These results contribute to the growing literature on leadership and innovation by highlighting the importance of psychological empowerment in driving innovative outcomes. The study also provides practical insights for organizational leaders to design leadership development programs that include self-leadership and inclusive leadership training, and create a work environment that encourages employee creativity and innovation by providing autonomy in decision-making, space to experiment with new ideas, and participatory communication.